Pelaksanaan Pembelajaran Menulis Cerita Pendek Pada Peserta Didik Kelas XI MAN 1 Kota Gorontalo: Penelitian - Kasiaradja, Syahrina; Malabar, Sayama; Ntelu, Asna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the learning activities of writing short stories for class XI students of MAN 1Kota Gorontalo , which consist of (1) how teachers plan the instruction of short story writing (2) how the instructional prosess is conducted in the classroom, (3) how studing writing is assessed, (4) what factors influence the instructional prosess, and (5) what solutions are implemented to overcome existing challenge. This study uses a descriptive method. There are three data collection techniques, namely documentation, observation, and interviews. Data analysis is carried out by identifying, classifying, describing, and drawing conclusions. The results of the study indicate that teachers have prepared learning plans in accordance with the independent curriculum through teaching modules that include learning objectives, learning activities, and learning assessments. The learning process is carried out by combining lecture methods, discussions, direct practice, and the use of learning media such as LCDs and teaching materials. Evaluation is carried out formatively and summatively through assessing the process and products of students' short stories. However, there are several obstacles that affect the effectiveness of learning, such as limited facilities, low learning motivation, lack of student confidence in writing, and limited mastery of linguistic structures and rules.